Student's perspective of politics / Muhammad Shodiiqurrohman Ahmad, Fauziah Ismail and Nur Syahirah Mohd Rodzi - Ahmad, Muhammad Shodiiqurrohman; Ismail, Fauziah; Mohd Rodzi, Nur Syahirah (2020)
Politics is a set of activities associated with the government of a country. Politics is important to each country especially the party because they will gain influence to have power in making law in the country. Every adult person should vote because our politics is our beliefs about how country have to be governed. Also, politics is important because it will affect by personal relationship between people who works together or separated. People should know about politics because we should make sure to all citizens to know there are rules and regulations to be follow. If citizen do not know about the law, then there will be punishment. In democracy, the citizens have the right to choose who to represent the government in the future by having elections that called Suruhanjaya Pllihan Raya (SPR).